Socialization of Academic Information System (SIKAD) as Transparency and Efficiency in Campus Services for Lombok Business Academy Students - Khairunnisah, Noni Antika; Nurfidah, Nurfidah; Damayanti, Sri; Junaedi, Junaedi; Azim, Muhammad; Alwyah, Lila (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The development of information technology has driven the transformation of the academic administration service system in higher education towards a more efficient and transparent direction. The Academic Information System (SIKAD) is present as a digital solution in managing academic data, which includes information on grades, attendance, class schedules, and other administrative processes. However, the level of student understanding and utilization of this system still needs to be improved. This community service activity aims to socialize the use of SIKAD to Lombok Business Academy students in order to create a comprehensive understanding of the functions and benefits of the system in supporting accountable and efficient academic processes. The implementation method includes delivering materials, demonstrating system usage, direct practice, and evaluation through discussions and questionnaires. The results of the activity show that students gain a better understanding of the features of SIKAD and realize the importance of this system in supporting openness and effectiveness of academic services. With this socialization, it is hoped that there will be an increase in student participation and independence in accessing academic information digitally and in real-time. This activity is also the first step in supporting digital transformation in the higher education environment, especially in efforts to realize transparent and technology-based academic administration governance.